1993
DOI: 10.1111/j.1365-2052.1993.tb00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of cDNA clones for chicken major histocompatibility complex class II molecules

Abstract: Sung, Aree Moon, "Isolation and characterization of cDNA clones for chicken major histocompatibility complex class II molecules " (1989). Retrospective Theses and Dissertations. 9089. http://lib.dr.iastate.edu/rtd/9089 INFORMATION TO USERSThe most advanced technology has been used to photo graph and reproduce this manuscript from the microfilm master. UMI films the text directly from the original or copy submitted. Thus, some thesis and dissertation copies are in typewriter face, while others may be from any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…A: Bursa of Fabricius; B: spleen; C: liver; D: thymus; E: glandular stomach; F: pancreas and duodenum. Iglesias et al, 2003;Juul-Madsen et al, 1993), single-strand conformation polymorphism (Goto et al, 2002), DNA sequence (Miller et al, 2004;Sung et al, 1993) and sequence-specific PCR (Livant and Ewald, 2005;Zheng et al, 1999). However, these methods are not always practical for large numbers of samples.…”
Section: Discussionmentioning
confidence: 99%
“…A: Bursa of Fabricius; B: spleen; C: liver; D: thymus; E: glandular stomach; F: pancreas and duodenum. Iglesias et al, 2003;Juul-Madsen et al, 1993), single-strand conformation polymorphism (Goto et al, 2002), DNA sequence (Miller et al, 2004;Sung et al, 1993) and sequence-specific PCR (Livant and Ewald, 2005;Zheng et al, 1999). However, these methods are not always practical for large numbers of samples.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated an association between the chicken MHC-B haplotype and resistance to various pathogens including Marek's disease virus, avian leukosis virus, Newcastle disease virus, Rous sarcoma virus, and Salmonella (Heinzelmann et al, 1981;Briles et al, 1982;Lamont, 1989;Dunnington et al, 1992;Yoo and Sheldon, 1992;Mays et al, 2005;Kim et al, 2008;Banat et al, 2013). Described in 1950 (Briles et al, 1950), at least 51 B haplotypes of the chicken B complex have been identified using traditional serological techniques (Briles and Briles, 1987;Landesman et al, 1993;Sung et al, 1993;Miller et al, 2004) or gene sequencing, RFLP, single-strand conformational poly-morphism, and SNP (Juul-Madsen et al, 1993;Fulton et al, 2006;Juul-Madsen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A minimum of six Class I genes (Kaufman et al, 1992) [20] and six Class II genes (Zoorob et al, 1993) [51] have been successfully replicated. The Class II /3 genes that are expressed appear to be grouped in a single isotope family (Pharr et al, 1993a;Sung et al, 1993) [34,41] . Polymorphisms in the putative antigen-binding site of chicken Class II have been found (Pharr et al, 1993b) [35] .…”
Section: The Major Histocompatibility Complex (Mhc)mentioning
confidence: 99%